2013
DOI: 10.1104/pp.113.225045
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cyclic GMP-Activated Nonselective Ca2+-Permeable Cation Channels and Associated CNGC5 and CNGC6 Genes in Arabidopsis Guard Cells    

Abstract: Cytosolic Ca2+ in guard cells plays an important role in stomatal movement responses to environmental stimuli. These cytosolic Ca 2+ increases result from Ca 2+ influx through Ca 2+ -permeable channels in the plasma membrane and Ca 2+ release from intracellular organelles in guard cells. However, the genes encoding defined plasma membrane Ca 2+ -permeable channel activity remain unknown in guard cells and, with some exceptions, largely unknown in higher plant cells. Here, we report the identification of two Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(98 citation statements)
references
References 102 publications
(181 reference statements)
1
97
0
Order By: Relevance
“…Current–voltage characteristics of CNGC18 in HEK293T cells (Gao et al ., ) are very similar to features of Ca 2+ ‐permeable channels in guard cells (Pei et al ., ; Wang et al ., ), root hair tips (Very & Davies, ), or PT tip protoplasts (Shang et al ., ; Qu et al ., ; Wu et al ., ). Recent genetic evidence points to CNGCs as prime candidates for pollen Ca 2+ ‐permeable channels in general and CNGC18 in particular (Wang et al ., ; Gao et al ., , ). Employing the combination of the TEVC technique and imaging would shed light on the contribution of the aforementioned GLRs and CNGCs to shape the apical Ca 2+ gradient.…”
Section: Discussionmentioning
confidence: 99%
“…Current–voltage characteristics of CNGC18 in HEK293T cells (Gao et al ., ) are very similar to features of Ca 2+ ‐permeable channels in guard cells (Pei et al ., ; Wang et al ., ), root hair tips (Very & Davies, ), or PT tip protoplasts (Shang et al ., ; Qu et al ., ; Wu et al ., ). Recent genetic evidence points to CNGCs as prime candidates for pollen Ca 2+ ‐permeable channels in general and CNGC18 in particular (Wang et al ., ; Gao et al ., , ). Employing the combination of the TEVC technique and imaging would shed light on the contribution of the aforementioned GLRs and CNGCs to shape the apical Ca 2+ gradient.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al . () found that CNGC5 and CNGC6 of A. thaliana guard cell PM are ABA‐insensitive, cGMP‐dependent Ca 2+ ‐permeable channels.…”
Section: Physiological and Structural Characteristics Of Plant Ca2+‐pmentioning
confidence: 99%
“…The CNGC5 and CNGC6 are required for cyclic GMP (cGMP)-activated nonselective Ca 2+ -permeable cation channel activity in the plasma membrane of A. thaliana guard cells and suggest CNGC5 and CNGC6 may also regulate Ca 2+ influx and Ca 2+ signaling (Finka et al 2012;Wang et al 2013). CNGC18 is expressed specifically in pollen and is required for polarized growth of pollen (Frietsch et al 2007).…”
Section: Introductionmentioning
confidence: 98%